Mrtvi iz prijedorskih grobišč kot relacijski akterji v povojni Republiki Srbski - Hamer, Petra (Svetovi (Ljubljana), 2026)
Article examines the roles of the dead in post-war Republika Srpska through the case of Prijedor. Human remains are not stable carriers of meaning, but relational mediators through which political narratives, collective memory, and national identities are formed. Their agency is distributed across actors, practices, and discourses, enabling the reworking of meanings and sustaining conflicting interpretations of the past. These processes are enacted through commemorations, exhumations, and the management of mass graves, where human remains become central sites of political and mnemonic contestation.
Keywords: Antropologija; collective memory; človeški ostanki; distributed agency; Etnična pripadnost; Etnologija; Grobnice; human remains; Kolektivna identiteta; kolektivni spomin; mass graves; množična grobišča; Mrtvi; Nacionalizem; nacionalna identiteta; national identity; Politične krize; porazdeljeno delovanje; Prijedor; Smrt; Trupla; Vojna hudodelstva